2013
DOI: 10.1097/lbr.0b013e3182a10b7a
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam in Flexible Bronchoscopy Premedication

Abstract: In our study, premedication with midazolam increased the patient-reported tolerance of the bronchoscopy. However, the absence of premedication did not affect the diagnostic yield of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Commonly experienced sensations included a terrible taste, feeling their throat was swollen, choking and inability to swallow. Discomfort relating to throat spray has been reported in other studies (Contoli et al, 2013;Lo et al, 2011), and an older study found that a significant number of patients with asthma had airway constriction related to the administration of local anaesthetic (McAlpine & Thomson, 1989). Similarly to the participants in our study, previous studies have reported shortness of breath, cough and sore throat associated with bronchoscopy (Houghton, Raghuram, Sullivan, & O'Driscoll, 2004;Ni, Lo, Lin, Fang, & Kuo, 2010).…”
supporting
confidence: 55%
“…Commonly experienced sensations included a terrible taste, feeling their throat was swollen, choking and inability to swallow. Discomfort relating to throat spray has been reported in other studies (Contoli et al, 2013;Lo et al, 2011), and an older study found that a significant number of patients with asthma had airway constriction related to the administration of local anaesthetic (McAlpine & Thomson, 1989). Similarly to the participants in our study, previous studies have reported shortness of breath, cough and sore throat associated with bronchoscopy (Houghton, Raghuram, Sullivan, & O'Driscoll, 2004;Ni, Lo, Lin, Fang, & Kuo, 2010).…”
supporting
confidence: 55%
“…However, this drug may depress the ventilatory drive and finally cause apnoea as its sedative pharmacology variability of different patients, especially in those with comorbidities and taking other respiratory depressant drugs at the same time. [25,26] As a short-acting and rapid recovery anesthetic agent, propofol has been widely used in many clinical fields such as gastrointestinal endoscopy, thyroplasty, bronchoscopy, interventional or radiological procedures, and awake bronchoscopy intubation for its hypnotic effect. However, because of the narrow therapeutic index between moderate sedation and respiratory depression, propofol is now strongly recommended for use only by anesthesiologists with close monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its short elimination half-life and a fast onset of action, midazolam is a first-choice drug among the benzodiazepines. However, its pharmacological effects vary among patients, and it may depress the ventilatory drive and finally cause apnea, especially in patients with co-morbidities who are taking other respiratory depressant drugs [20, 21]. As a short-acting anesthetic agent with rapid recovery, propofol has been widely used in many clinical fields such as gastrointestinal endoscopy, thyroplasty, bronchoscopy, interventional or radiological procedures, and during awake bronchoscopy intubation, for its hypnotic effect [22, 23].…”
Section: Discussionmentioning
confidence: 99%